The Role Of Islamic Banking In The Development Of Islamic Economic Progress In Indonesia - Efendi Sugianto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Economic activities that lead to Islamic Economics or Sharia Economics are increasingly spreading throughout the world, including Indonesia. Sharia economics is an economic system based on sharia values ​​and principles originating from the teachings of the Islamic religion. Experts also define sharia economics. The sharia economy has its own characteristics that differentiate it from other economies. Sharia economics originates from the Koran, hadith or sunnah, ijmak and qiyas. The goal of sharia economics is to achieve happiness in this world and the hereafter through a good and honorable way of life. There are many activities in the sharia economy, one of which is sharia banking. Where sharia economics and sharia banking are closely related to each other. Sharia banking is an example of Sharia Economics. This research uses qualitative research methodology. This research uses descriptive analysis to describe and analyze the data obtained. The results of this research can be used as a basis for policy development, service improvements, or a better understanding of sharia economics in general